Associations between psychophysiological stress responses, inflammatory markers, and CSF biomarkers in the spectrum of Alzheimer's disease. (31st December 2021) - Oh, Hwamee; Leung, Hoi‐Chung; Canli, Turhan; Slifstein, Mark; Park, Elliot Y.
Abstract: Background: Although genetic factors associated with the aggregation of misfolded proteins clearly play a role in Alzheimer's disease (AD), several individual difference factors have been seen to confer an increased risk for the clinical manifestation of AD as well as the development of AD pathology. One of the key factors is an individual's susceptibility to psychological stress. The goal of this study was to examine the relationships between psychophysiological stress responses measured by plasma stress hormones and neuropsychiatric symptoms, inflammatory markers, and AD pathology along the spectrum of AD. Method: Alzheimer's Disease Neuroimaging Initiative (ADNI) consists of 819 adult subjects— 229 cognitively normal older adults (CNs), 398 participants with mild cognitive impairment (MCIs), and 192 patients with AD. Of these subjects, we included 58 CNs, 396 MCIs, and 112 AD patients whose plasma stress measures were available. Plasma cortisol and cytokines and CSF Aβ1‐42, t‐tau, and p‐tau181 data were downloaded from ADNI. Neuropsychiatric Inventory (NPI‐Q) total scores were used to indicate a psychological stress level. Result: AD stages were significantly related to the level of plasma cortisol and NPI‐Q total scores showing that AD patients exhibit the highest level of cortisol and greater severity of psychological symptoms followed by MCIs and CNs. AD stages were also significantly related to the level of inflammatory markers measured by cytokines, although the level of inflammatory markers in relation to the diagnostic groups varied across different types of cytokines. Plasma cortisol levels did not relate to concurrent levels of CSF Aβ1‐42 either across diagnostic groups or within diagnostic groups. Higher plasma cortisol, however, corresponded to higher CSF p‐tau among CNs, but not in MCIs and ADs. Conclusion: Psychophysiological stress responses and inflammatory markers are significantly associated with the disease severity. A positive relationship between plasma cortisol level and CSF p‐tau in CNs may indicate a role of individuals' susceptibility to stress in neuronal hyperexcitability in the early stage of AD and confer a risk of neurodegeneration and the development of AD. Alleviating stress and regulating stress responses may be important modifiable factors that help prevent AD.